Has Boston's 2011 cigar packaging and pricing regulation reduced availability of single-flavoured cigars popular with youth?. Issue 2 (6th April 2016) - Li, Wenjun; Gouveia, Tami; Sbarra, Cheryl; Harding, Nikysha; Kane, Kevin; Hayes, Rashelle; Reid, Margaret
Abstract : Objective: We evaluated retailer compliance with a cigar packaging and pricing regulation in Boston, Massachusetts, enacted in February 2012, and the regulation's impact on availability of single cigars. Methods: Grape-flavoured Dutch Masters (DM) single-packaged cigars were examined as market indicator. At quarterly intervals from October 2011 to December 2014, availability and price of DM single cigars were observed through professional inspector visits to tobacco retailers in Boston (n=2232) and 10 comparison cities (n=3400). Differences in price and availability were examined between Boston and the comparison cities and across Boston neighbourhoods. Results: The mean price of DM single cigars sold in Boston increased from under 1.50 in 2011 to above 2.50 in 2014, consistent with regulation requirements. Rates of retailer compliance reached 100% within 15 months postpolicy enactment based on observed price, and 97% at 30 months postenactment based on final sale prices. There was a 34.5% net decrease in the percentage of Boston retailers selling single cigars from 2011 to 2014. The number of Boston neighbourhoods with 3 or more retailers selling single cigars per 100 youth residents decreased from 12 in 2011 to 3 in 2014. No change in price or per cent of retailers selling single cigars was observed in the comparison cities in the same period. Conclusions: Retailers throughout Boston are in compliance with the regulation. The regulation has been effective in reducing levels and disparities in availability of flavoured single cigars popular with youth across Boston neighbourhoods, regardless of socioeconomic status and racial/ethnic composition.